Combination of BMP2 and MSCs Significantly Increases Bone Formation in the Rat Arterio-Venous Loop Model - Bührer, Gregor; Balzer, Amelie; Arnold, Isabel; Beier, Justus; Körner, Carolin; Bleiziffer, Oliver; Brandl, Andreas; Weis, Christian; Horch, Raymund E.; Kneser, Ulrich; Arkudas, Andreas (Tissue Engineering - Part A, 2015)

Dislocation of the PIP-Joint - Treatment of a common (ball)sports injury - Müller-Seubert, Wibke; Bührer, Gregor; Horch, Raymund E. (Sportverletzung-Sportschaden, 2017)
Background Fractures or fracture dislocations of the proximal interphalangeal joint often occur during sports or accidents. Dislocations of the PIP-joint are the most common ligamentary injuries of the hand. As this kind of injury is so frequent, hand surgeons and other physicians should be aware of the correct treatment.Objectives This paper summarises the most common injury patterns and the correct treatment of PIP-joint dislocations.Materials and Methods This paper reviews the current literature and describes the standardised treatment of PIP-joint dislocations.Results What is most important is that reposition is anatomically correct, and this should be controlled by X-ray examination. Depending on the instability and possible combination with other injuries (e. g. injury to the palmar plate), early functional physiotherapy of the joint or a short immobilisation period is indicated.Conclusions Early functional treatment of the injured PIP-joint, initially using buddy taping, is important to restore PIP-joint movement and function. Depending on the injury, joint immobilisation using a K-wire may be indicated. Detailed informed consent is necessary to explain to the patient the severity of the injury and possible complications, such as chronic functional disorders or development of arthrosis.
EVALuna2:32840

Evaluation of angiogenesis of bioactive glass in the arteriovenous loop model - Arkudas, Andreas; Balzer, Amelie; Bührer, Gregor; Arnold, Isabel; Hoppe, Alexander; Detsch, Rainer; Newby, Phillipa; Fey, Tobias; Greil, Peter; Horch, Raymund E.; Boccaccini, Aldo R.; Kneser, Ulrich (Tissue Engineering - Part C: Methods, 2013)
In this study, the angiogenetic effect of sintered 45S5 Bioglass (R) was quantitatively assessed for the first time in the arteriovenous loop (AVL) model. An AVL was created by interposition of a venous graft from the contralateral side between the femoral artery and vein in the medial thigh of eight rats. The loop was placed in a Teflon isolation chamber and was embedded in a sintered 45S5 Bioglass (R) granula matrix filled with fibrin gel. Specimens were investigated 3 weeks postoperatively by means of microcomputed tomography, histological, and morphometrical techniques. All animals tolerated the operations well. At 3 weeks, both microcomputed tomography and histology demonstrated a dense network of newly formed vessels originating from the AVL. All constructs were filled with cell-rich, highly vascularized connective tissue around the vascular axis. Analysis of vessel diameter revealed constant small vessel diameters, indicating immature new vessel sprouts. This study shows for the first time axial vascularization of a sintered 45S5 Bioglass (R) granula matrix. After 3 weeks, the newly generated vascular network already interfused most parts of the scaffolds and showed signs of immaturity. The intrinsic type of vascularization allows transplantation of the entire construct using the AVL pedicle.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.evalua

Intraoperative flap design using ICG monitoring of a conjoined fabricated anterolateral thigh/tensor fasciae latae perforator flap in a case of extensive soft tissue reconstruction at the lower extremity - Bührer, Gregor; Taeger, Christian; Ludolph, Ingo; Horch, Raymund E.; Beier, Justus (Microsurgery, 2016)
In this report, we present a case of the use of a conjoined fabricated free anterolateral thigh (ALT)/tensor fascia latae (TFL) perforator flap for reconstruction of the lower extremity with intraoperative flap design using intraoperative indocyanine green (ICG) monitoring. The flap was used for reconstruction of a 16 cm × 28 cm sized defect of the lower leg in a 24-year-old man. The defect was caused by a third degree open fracture to the tibia. Upon dissection of the ALT perforators, ICG monitoring showed that both dominant ALT perforators did not yield a sufficient perforasome ( 16 cm × 17 cm) for the larger flap needed. An adjacent TFL perforator also supplied a large perforasome ( 15 cm × 11 cm), so a conjoined fabricated flap was harvested and transplanted to cover an extensive lower leg defect. The artery of the TFL perforator pedicle was being in-flap anastomosed to a side branch of the ALT pedicle. Postoperative course was uneventful and there were no complications. Length of follow-up was 6 months, aesthetic and functional outcome was good. The patient was very satisfied with the aesthetic outcome. Both legs were fully mobile after intensive physiotherapy for the reconstructed leg. The leg where the flap had been harvested showed full strength in knee joint flexion. This case could show that identification of the supplying vessels may be possible by ICG monitoring. © 2015 Wiley Periodicals, Inc. Microsurgery 36:684-688, 2016.
EVALuna2:15607

Irrigation of chronic wounds with tap water as a prerequisite for improved healing - Hillenbrand, Matthias; Bührer, Gregor; Horch, Raymund E. (International Wound Journal, 2014)
EVALuna2:15570

Less is more – retrospective comparison of shoulder strength and range of motion between conventional and muscle-sparing harvesting technique of a latissimus dorsi flap - Müller-Seubert, Wibke; Scheibl, Karsten; Bührer, Gregor; Möbius, Cornelia; Ludolph, Ingo; Horch, Raymund E.; Arkudas, Andreas (Journal of Plastic Reconstructive and Aesthetic Surgery, 2021)
Background: The muscle-sparing latissimus dorsi flap poses an alternative to the conventional latissimus dorsi flap when a defect requires a smaller flap volume with a long vascular pedicle. The aim of the study was to analyze the functional outcome following muscle-sparing versus conventional harvest of a latissimus dorsi flap. Material and Methods: Patients who received a muscle-sparing latissimus dorsi muscle flap transplantation (group 1) and patients with a complete latissimus dorsi muscle flap harvest (group 2) for defect reconstruction at the University Hospital of Erlangen between 2007 and 2016 were examined. The evaluation included a physical examination with the measurement of strength and range of motion of the shoulder of both the donor side as well as the nonoperated side. Furthermore, the DASH score was evaluated. Additionally, patients in group 1 received a neurophysiological examination. Results: The DASH score did not show statistically significant differences between both groups. Both strength (p = 0.031) and range of motion (p<0.05) of the shoulder of the donor side were statistically significantly lower than the nonoperated side in group 2, while no difference was found in group 1. The neurophysiological examination in group 1 showed a reduced nerve conduction velocity of the donor side as compared to the nonoperated side in most patients (60% and n = 3). Conclusion: Harvesting the muscle-sparing latissimus dorsi flap leads to less functional impairments of the shoulder than harvesting the complete latissimus dorsi flap.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Defect reconstruction; Functional impairment; Latissimus dorsi flap; Muscle sparing latissimus dorsi flap

Merkel Cell Carcinoma - A Rare Entity with Specific Reconstructive Challenges - Bührer, Gregor; Horch, Raymund E.; Schlabrakowski, Anne; Arkudas, Andreas (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2016)
Merkel cell carcinoma is a rare tumor, which is associated with poor prognosis. It has been shown that radical local excision and radiotherapy are essentiell for curative therapy. To avoid compromise in tumor treatment, plastic surgery is often needed. Furthermore, using complex reconstruction methods, like free flap transplantation, has proven to be effective to avoid long and complicated clinical courses.Between 2003 and 2016 15 patients with Merkel cell carcinoma were treated in our department. In 2 cases additional resection had to take place before reconstruction was performed. In most cases, a safety margin of 2 cm was chosen. Complete excision could be achieved in 13 patients. We used different methods of reconstruction such as primary suturing, skin transplantations, local, pedicled or free flaps.In all patients defects could be reconstructed with good results, which proved to be stable even under postoperative radiation therapy.Given the modern techniques of plastic surgery the extent of local excision should not be should be chosen as radical as possible and necessary. It has been proven that interdisciplinary treatment of patients with Merkel cell carcinoma increases the chances for curative therapy while providing safe methods for reconstruction despite radiotherapy, extensive tumors or difficult localization.
EVALuna2:6765

Pedicled Transplantation of Axially Vascularized Bone Constructs in a Critical Size Femoral Defect - Arkudas, Andreas; Lipp, Amelie; Bührer, Gregor; Arnold, Isabel; Davinova, Diana; Brandl, Andreas; Beier, Justus; Körner, Carolin; Lyer, Stefan; Alexiou, Christoph; Kneser, Ulrich; Horch, Raymund E. (Tissue Engineering: Parts A, B, and C, 2017)
Introduction: Axial vascularization represents a mandatory requirement for clinically applied larger scale vascularized bone grafts. The aim of this study was to combine the arteriovenous (AV) loop model in the rat with a critically sized femoral bone defect and to successfully transplant axially vascularized bone constructs into the defect. Materials and Methods: In Groups A and C, an AV loop together with a clinically approved hydroxyapatite and beta-tricalcium phosphate (HA/β-TCP) matrix, mesenchymal stem cells, and recombinant human bone morphogenetic protein 2 were implanted into a newly designed porous titanium chamber with an integrated osteosynthesis plate in the thighs of rats, whereas in Groups B and D, the same matrix composition without AV loop and, in Group E, only the HA/β-TCP matrix were implanted. After 6 weeks, the constructs were transplanted into a 10 mm femoral defect created in the same leg, in Groups A and C, under preservation of the AV loop pedicle. Group F served as a control group with an empty chamber. Ten days (Groups A and B) and 12 weeks (Groups C–F) after transplantation, the femora together with the constructs were explanted and investigated using computed tomography (CT), micro-CT, X-ray, histology, and real-time polymerase chain reaction (RT-PCR). Results: Ten days after transplantation, Group A showed a maintained vascular supply leading to increased vascularization, cell survival in the scaffold center, and bone generation compared to Group B. After 12 weeks, there was no difference detectable among all groups regarding total vessel number, although Group C, using the AV loop, still showed increased vascularization of the construct center compared to Groups D and E. In Group C, there was still enhanced bone generation detectable compared to the other groups and increased bony fusion rate at the proximal femoral stump. Conclusions: This study shows the combination of the AV loop model in the rat with a critically sized femoral defect. By maintenance of the vascular supply, the constructs initially showed increased vascularization, leading to increased bone formation and bony fusion in the long term.
Keywords: AV loop; femur defect model; critically sized bone defect; bone tissue engineering

Reconstruction of Extensive Volar Finger Defects with Double Cross-Finger Flaps - Bührer, Gregor; Arkudas, Andreas; Ludolph, Ingo; Horch, Raymund E.; Taeger, Christian (Plastic and Reconstructive Surgery Global Open, 2016)
Cross-finger flaps still represent a viable option to reconstruct small- to medium-sized full-thickness finger defects but they are not commonly used if larger areas have to be covered. We present 2 cases showing a simple and pragmatic approach with homodigital double cross-finger flaps to reconstruct extensive volar finger soft-tissue defects. We observed very low donor-site morbidity and excellent functional and aesthetic outcomes. Furthermore, there is no need for microsurgical techniques or equipment when using this method. Although this case report only addresses volar defects, one might also think of applying this concept to dorsal defects using reversed double cross-finger flaps.
CRIS-Team Scopus Importer:2025-05-07

Surgical treatment of burns : Special aspects of pediatric burns - Bührer, Gregor; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas (Hautarzt, 2017)
BACKGROUND: Treatment of pediatric burn patients is very important because of the sheer frequency of burn wounds and the possible long-term ramifications. Extensive burns need special care and are treated in specialized burn centers. OBJECTIVES: The goal of this work is to present current standards in burn therapy and important innovations in the treatment of burns in children so that the common and small area burn wounds and scalds in pediatric patients in day-to-day dermatological practice can be adequately treated. MATERIALS AND METHODS: Analysis of current literature, discussion of reviews, incorporation of current guidelines. RESULTS: Burns in pediatric patients are common. Improvement of survival can be achieved by treatment in burn centers. The assessment of burn depth and area is an important factor for proper treatment. We give an overview for outpatient treatment of partial thickness burns. New methods may result in better long-term outcome. CONCLUSIONS: Adequate treatment of burn injuries considering current literature and guidelines improves patient outcome. Rational implementation of new methods is recommended.
EVALuna2:32844

Treatment of standardised wounds with pure epidermal micrografts generated with an automated device - Bührer, Gregor; Arkudas, Andreas; Horch, Raymund E. (International Wound Journal, 2017)
In this study, we analysed the effects of pure epidermal micrografts generated with an automated device in a standardised human wound model. Epidermal micrografts were harvested using an automated device. Micrografts were then transplanted onto split-skin donor sites. The target area was only partially covered with transplants to create an intra-individual control area. Wounds were evaluated by subjective assessment as well as measurements with combined laser and white light spectroscopy and cutometry. The epidermal graft sites remained completely stable, whereas control sites offered partially unstable and blistering areas. Statistically, no measurable difference in the speed of initial reepithelialisation could be shown. However, there was an increased pliability and softness of the treated areas that correlated with the subjective impression of both investigators and patients. There was a significantly higher relative haemoglobin concentration, measurable in treated and untreated areas at 4 weeks and 6 months. Cutometry showed no differences in skin properties between treated and untreated areas. This study shows an effect of epidermal micrografts in a standardised human wound model and supports the positive impact of keratinocytes on early wound healing as described in literature. Long-term effects of epidermal grafting deserve further studies.
EVALuna2:32837